RANCANG BANGUN PROTOTYPE SMART GREENHOUSE MENGGUNAKAN THINGSPEAK - Raihan Nurfarisi; Alfian, Andi; Tri Ferga Prasetyo (Universitas Majalengka, 2024)
The design of this smart greenhouse prototype is one of the implementations of artificial intelligence controlled by the Arduino uno microcontroller, which has actuators in the form of lights and pumps and is equipped with DHT22 sensors, Soil Moisture and Temperature Sensors. The method used in making this smart greenhouse prototype is the Prototype method. There are seven stages in the prototype method that guide the process of making robots, namely gathering requirements, building prototypes/prototypes, evaluating prototypes, programming systems, testing systems, evaluating systems, and using the system. The most important stage in making this smart greenhouse prototype is the stage where at this stage testing is carried out on the results of the design and programming of the robot that has been made to prove the robot prototype is in accordance with what is desired or not. The testing process is carried out in tandem with the assembly process and programming process. In the process of assembling and programming the robot prototype, it is done with system errors. Testing with system errors is carried out to get a robot prototype that works optimally.